1999
DOI: 10.1203/00006450-199906000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-12 in Human Milk

Abstract: The presence of interleukin-12 (IL-12) in 39 samples of human milk was investigated using the enzyme-linked immunosorbent assay. IL-12 (>40 pg/mL) was detected in 24 of the 39 samples collected (1408 +/- 2256 pg/mL, mean +/- SD, n = 24). A range of concentrations of IL-12 was observed in colostrum, transitional, and mature milk, with an apparent decrease in the mean concentration over time postpartum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 16 publications
2
22
0
Order By: Relevance
“…Böttcher et al [22] reported no differences for TGF-b. In agreement with our findings, a small study found no associations between IL-12 in breast milk and a maternal atopic status [23]. Our findings of higher levels of sCD14 in mothers with a maternal allergic history (P = 0.04) or mothers with sensitization (P = 0.03) have not been reported earlier.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Böttcher et al [22] reported no differences for TGF-b. In agreement with our findings, a small study found no associations between IL-12 in breast milk and a maternal atopic status [23]. Our findings of higher levels of sCD14 in mothers with a maternal allergic history (P = 0.04) or mothers with sensitization (P = 0.03) have not been reported earlier.…”
Section: Discussionsupporting
confidence: 92%
“…More recently, Rothenbacher et al [15] found a lower risk for atopic eczema for breastfed infants (X6 months, sCD14 in the highest quartile) vs. less than 3 months' breastfeeding. They suggested that the beneficial [23,33,34] or TGF-b1 [8,9,22,24,32,35,36] concentrations in breast milk with inconsistent results with respect to the mothers and/or infant's atopic outcomes. We speculate that three explanations may clarify these inconsistencies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggested that high levels of IL-18 were associated with preterm delivery, which was closely associated with pregnancy complications. Figure 2, colostrum contained TNF-␣, IL-12, IFN-␥, and sFasL, as reported previously (10,11). TNF-␣ levels in colostrum were higher in mothers with preterm delivery than in those with delivery at term, whereas IL-12, IFN-␥, and sFasL levels showed no significant differences between those with preterm and term delivery.…”
Section: Il-18 Levels Of Human Milksupporting
confidence: 66%
“…Moreover, as levels of immune markers may vary in time (16)(17)(18)(19), we tested whether the levels of immune mediators correlated with the interval of collection after birth. None of the immune markers were correlated with the time of milk collection, which is in agreement with a recent review on breast milk immune markers (20).…”
Section: Articlesmentioning
confidence: 99%